Pengaruh Dosis Kompos dan Frekuensi Penyiraman pada Pertumbuhan Bibit Sengon Laut (Paraserianthes falcataria L.) - Petrus Tefa; Roberto I. C. O. Taolin; Maria Afnita Lelang (Savana Cendana, 2016)
This study aims to determine the effect of compost dosage and the frequency of watering on the growth of Sengon Laut seedlings as well as to know compost dose and watering frequency that proper for optimum growth of Sengon Laut seedlings. The study used Randomized Block Design Factorial with three replications. The first factor is a compost dose consisting of three levels of control or 0 g per polybag, 30 g per polybag and 40 g per polybag. The second factor is the frequency of watering which consists of three levels ie twice a day, once a day and once in two days. The results showed no interaction effect between compost dose and frequency of watering on all parameters. The compost dose significantly affected the plant height parameters at each observation time, the diameter of the stem at each observation time, the fresh weight of the seedlings and the dry weight of the seedlings. The watering frequency had a significant effect on soil temperature 60 days after transplanting (DAT) and 90 DAT, plant height 30 DAT, stem diameter 30 DAT and 60 DAT. Compost dose of 30 g per polybag is the optimum dose for the growth of sengon seedlings while watering twice a day is the right watering frequency for the seedlings of sengon.